LAND SUITABILITY EVALUATION FORORANGE FRUITCROP AT THE SEMELAGI KECILVILLAGE DISTRICT SINGKAWANG UTARA - adilia, prihayu; Rini, Hazriani; Ari, Krisnohadi (Jurnal Sains Pertanian Equator, 2017)
ABSTRACT : Land is a natural resource which is very important foragriculture and. This study aims to determine the level of land suitability classes as well as inhibited factorsfor orange fruit crop. Land to be evaluated is located in the village of Semelagi Kecil district Singkawang Utara. Parameter study include ; state of the environment, physic, and chemical properties of the soil. The environment factors are and topography, climate, the flooding , drainage, land use. Soil physic properties observed color of soil, soil texture and structure of soil, groundwater level, depth of sulfidic and effective depth, ripeness soil,and kosistensi soil. Soil chemical properties in laboratory analysis, including pH, CEC, KB, Organic C, total-N, P, K, Ca, mg and Salinity.The results showed that among the sites there are two soil mapping unit (SPT) is Typic Endoaquepts that have actual land suitability classes S3.b, potential land class suitability S1with a land area of ± 125 ha of the total area of "‹"‹the research sites.Recommended management consists of recommendations for improvement of drainage and guludan, liming, fertilizzation. Drainage improvements as it has drainage freewheeling, the ground water level ranges from >120 cm. Soil pH 5,62, need to improved with liming and fertilizzation. The calculation is done based on the levels of Al -dd at the ground surface. Lime used is Calsit limestone (CaCO3). In SPT lime and fertilizer needs can be given in accordance with the recommendations of the government in general. Key word : Orange, Land Suitability Evaluation.